Semaglutide promotes the proliferation and osteogenic differentiation of bone-derived mesenchymal stem cells through activation of the Wnt/LRP5/β-catenin signaling pathway - Tian, Yawei; Liu, Huiming; Bao, Xiaoxue; Li, Yukun (Frontiers in Pharmacology, 2025)
Diabetes mellitus is a global disease in which alterations in the internal environment disrupt the bone-fat balance, contributing to osteoporosis. Semaglutide, a single-target, long-acting glucagon-like peptide-1 receptor agonist (GLP-1RA), has been shown to promote osteogenesis in vitro, but the underlying mechanism remains unclear. In this study, the ability of Semaglutide to promote the proliferation of bone-derived mesenchymal stem cells (BMSCs) was determined by CCK-8 kit and flow cytometry, Alkaline phosphatase (ALP) staining and alizarin red S staining showed that semaglutide increased ALP activity and the proportion of mineralised nodules during induction of osteogenesis, wound healing assay to evaluate the pro-migratory ability of semaglutide on BMSCs.Western blotting and RT-PCR showed that semaglutide promoted the mRNA and protein expression of osteocalcin (OCN) and Runt-related transcription factor 2 (RUNX2), and further determined the OCN expression level by immunofluorescence. RNA sequencing was performed to analyze the mechanisms underlying BMSC osteogenesis after semaglutide intervention. Enrichment of RNA sequencing data indicated that the Wnt/LRP5/β-catenin pathway was activated after treatment with semaglutide. Western blotting further confirmed the upregulation of Wnt pathway-associated protein levels by semaglutide. Dickkopf-1 (DKK1) and LiCl (lithium chloride) are common inhibitors and agonists of the Wnt/β-catenin pathway. The addition of semaglutide resulted in the partial reversal of the inhibitory effect of DKK1 on osteogenic differentiation, with the administration of LiCl and semaglutide further accelerating the osteogenic process. In addition to alterations in gene and protein expression levels, these changes are also reflected in alkaline phosphatase (ALP) activity and calcium deposition. Therefore, we suggest that semaglutide can promote the proliferation and osteogenic differentiation of BMSCs in vitro via the Wnt/LRP5/β-catenin signalling pathway.